Geological constraints on hydrocarbon contacts in the greater Norne area - Osnes, Max Osen (The University of Bergen, 2018)
The understanding of the geological constraints on the position of fluid contacts is important for the evaluation of the remaining resources on the Norwegian Continental Shelf. Different mechanisms can lead to filled, underfilled or overfilled traps. This can greatly affect the inplace volumes of hydrocarbons in a prospect. The study investigates the position of hydrocarbon water contacts and spill points in 10 individual structures situated on the western edge of the Nordland Ridge and on the Dønna Terrace. A detailed geological mapping of the reservoirs in the area was conducted by the interpretation of high resolution 3D-seismic data. Available data from exploration wells was utilized to estimate shale smear factors for critical faults, investigate formation pressures and determine the depths of hydrocarbon-water contacts. The high overpressures in the Cretaceous Reservoirs on the Dønna Terrace falls on a pressure gradient defined for overpressured structures on Haltenbanken, and some of the structures are most likely underfilled. The structures included in the commonly accepted Norne fill-spill route, are all in pressure communication with the surface. Most of the traps are filled to spill, but some are overfilled relative to their structural spill point. The Cretaceous reservoirs on the Dønna Terrace has probably leaked either through cap rock failure or fault reactivation. The Norne fill-spill route is confirmed as the most likely model for the structures suggested to be on this migration route. Sealing faults are in some locations critical for the fill spill route to work. Masteroppgave i geovitenskap MAMN-GEOV GEOV399